2018
DOI: 10.1002/admi.201701299
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Temperature Graphene Molecular Heater

Abstract: for metal films, [10] which are the basic building blocks of traditional heaters, after reducing the thickness strongly inhibits the realization of molecular heaters. Therefore, it is of great importance to find a satisfactory molecular building block with thicknesses controlled at the atomic level and unique electrical properties to achieve the construction of molecular heater.Graphene, which can be considered as a polycyclic aromatic hydrocarbon molecule with strictly atomic thickness, has been known as an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…To minimize the contact resistance between electrodes and graphene, a 1D edge coupling approach [ 86 ] or patterning the electrodes [ 87 ] could reduce the total voltage required to dissipate P Am on the heater. Morever, to avoid the current saturation and reach high temperatures, multi‐layer graphene could be used, [ 88 ] and hexagonal boron nitride encapsulated graphene devices can be used as they sustain high lattice temperature up to ≈1600 K. [ 66 ] Finally, to reduce the sheet resistance and also avoid the current saturation, a gate terminal could be added to control the charge doping of graphene. [ 60 ]…”
Section: Multi‐physics Simulation Modelmentioning
confidence: 99%
“…To minimize the contact resistance between electrodes and graphene, a 1D edge coupling approach [ 86 ] or patterning the electrodes [ 87 ] could reduce the total voltage required to dissipate P Am on the heater. Morever, to avoid the current saturation and reach high temperatures, multi‐layer graphene could be used, [ 88 ] and hexagonal boron nitride encapsulated graphene devices can be used as they sustain high lattice temperature up to ≈1600 K. [ 66 ] Finally, to reduce the sheet resistance and also avoid the current saturation, a gate terminal could be added to control the charge doping of graphene. [ 60 ]…”
Section: Multi‐physics Simulation Modelmentioning
confidence: 99%
“…Investigators have reported various techniques to exploit graphene as the microheater for GST mediums [40][41][42][43] . In this stream, Rios et al 37 demonstrated the optoelectronic framework incorporating undoped monolayer graphene heater to perform reversible and controllable switching between four different levels of crystallinity for a large area of GST medium.…”
Section: Openmentioning
confidence: 99%
“…41 discusses the techniques to enhance the Joule performance of graphene heater, and reports on decreasing the sheet resistance and minimizing the contact resistance between graphene layer and electrodes. Within the context, the sheet resistance of graphene is inversely related to its bidimensional conductivity-the factor that can be defined by the electron relaxation time and the numbers of layers 33,42 . Hung et al 42 showed that increasing the number of graphene layers up to 4, thereby contributing to nearly 1 nm total thickness, would increase the Joule performance; a high temperature up to 600 °C can be achieved at a low voltage of 4.3 V. However, they showed that the use of graphene layer thickness > 1 nm slightly increases the sheet resistance (of heater) since the increased edge structure would reduce the heating efficiency.…”
Section: Openmentioning
confidence: 99%
“…Due to their excellent electrical conductivity and thermal conductivity [ 5 , 6 , 7 , 8 ], they were involved in many researches on functional materials. Of which, electrothermal functional composite can convert electrical energy into thermal energy on the basis of Joule heating principle principally due to the inelastic collision of charged particles under the electric field [ 9 ]. Recently, related studies reported various electrothermal composites made of CNTs or GP, which can be used for medical infusion apparatus [ 10 ], deicing [ 11 , 12 ], defrosting and defogging [ 13 , 14 , 15 ], repairing and self-curing resin [ 16 ], and other fields [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%